Administrative data linkage as a tool for developmental and life-course criminology: The Queensland Linkage Project. Issue 3 (September 2015) - Stewart, Anna; Dennison, Susan; Allard, Troy; Thompson, Carleen; Broidy, Lisa; Chrzanowski, April
A fundamental challenge to developmental and life-course (DLC) criminology research is access to appropriate longitudinal data to examine hypotheses concerning causal risk factors for offending and within-individual change over time, and to empirically test DLC theories. In this paper we present a powerful method for collecting appropriate data – linked administrative data. The Queensland Linkage Project includes three population-based longitudinal linked administrative databases – the Queensland Longitudinal Data (QLD) – QLD 83, QLD 84 and QLD 90. We describe the methodology of linking administrative data, the establishment of the QLD datasets and a selection of the work facilitated by these data. This work addresses issues raised by the editors including the effects of life events and the timing of risk factors (child maltreatment) on further offending, the monetary costs of offending across the life-course and the development of adult-onset offending. We finish by describing current work on the Queensland Linkage Project where mental health system data are being integrated with justice system data.